Motivasi Diri Melalui Gadget Untuk Membentuk Karakter Dan Kompetensi Remaja - Caniago, Rita Srihasnita Rosali; Sulistyaningsih, Heni; Chairoel, Lucy; Maivalinda, Maivalinda; Turay, Tiara; Firsta, Firsta; Riski, Tri Rachmat; Utami, Dwi Tyas; Imbikri, M (LPPM Universitas Dharma Andalas, 2025)
The development of information and communication technology is one of the important factors in supporting the availability of student accessibility to every information obtained through the use of electronic devices (gadgets). Students' ability to sort academic information is expected to be able to provide reinforcement in broadening students' perceptions in producing a more practical and innovative learning approach. Students of SMA 4 and SMKN 5 Sijunjung Regency are schools with A accreditation qualifications that have students with the Z generation category who have a reflection as a generation that is very strongly involved in the development of information technology. The strong involvement of Generation Z students in the use of Gadgets is the main factor in identifying student motivation, attitudes and behavior in the use of Gadgets, thus having an impact on student learning productivity for every information received. The approach of self-motivation training, life skills, soft skills and hard skills is the initial approach in directing students persuasively in understanding the benefits of the availability of information access, especially in increasing student information and knowledge. The results of the activity show that the persuasive approach carried out during the training process is able to attract positive responses from students, especially for every material that is related to the world of Generation Z teenagers. These results also show that a persuasive, innovative and relational approach is able to increase the enthusiasm of Generation Z students for every information that is academic and educational.